Deep brain stimulation of the subcallosal cingulate for treatment-refractory anorexia nervosa: 1 year follow-up of an open-label trial. (April 2017) - Lipsman, Nir; Lam, Eileen; Volpini, Matthew; Sutandar, Kalam; Twose, Richelle; Giacobbe, Peter; Sodums, Devin J; Smith, Gwenn S; Woodside, D Blake; Lozano, Andres M
Summary: Background: Anorexia nervosa is a life-threatening illness. Brain circuits believed to drive anorexia nervosa symptoms can be accessed with surgical techniques such as deep brain stimulation (DBS). Initial results suggest that DBS of the subcallosal cingulate is safe and associated with improvements in mood and anxiety. Here, we investigated the safety, clinical, and neuroimaging outcomes of DBS of the subcallosal cingulate in a group of patients during 12 months of active stimulation. Methods: We did this prospective open-label trial at the Department of Surgery of the University of Toronto (Toronto, ON, Canada). Patients were eligible to participate if they were aged 20–60 years and had a diagnosis of anorexia nervosa (restricting or binge–purging subtype) and a demonstrated history of chronicity or treatment resistance. Following a period of medical stabilisation, patients underwent surgery for DBS and received open-label continuous stimulation for the entire 1 year study duration. The primary outcome was safety and acceptability of the procedure. The secondary outcomes were body-mass index (BMI), mood, anxiety, affective regulation, and anorexia nervosa-specific behaviours at 12 months after surgery, as well as changes in neural circuitry (measured with PET imaging of cerebral glucose metabolism at baseline and at 6 and 12 months after surgery). This trial was registered withClinicalTrials.gov, numberNCT01476540 . Findings: 16 patients with treatment-refractory anorexia nervosa were enrolled between September, 2011, and January, 2014, and underwent DBS of the subcallosal cingulate between November, 2011, and April, 2014. Patients had a mean age of 34 years (SD 8) and average illness duration of 18 years (SD 6). Two patients requested that their devices be removed or deactivated during the study, although their reasons for doing so were poorly defined. The most common adverse event was pain related to surgical incision or positioning that required oral analgesics for longer than 3–4 days after surgery (five [31%] of 16 patients). Seven (44%) of 16 patients had serious adverse events, most of which were related to the underlying illness, including electrolyte disturbances. Average BMI at surgery was 13·83 (SD 1·49) and 14 (88%) of the 16 patients had comorbid mood disorders, anxiety disorders, or both. Mean BMI after 12 months of stimulation was 17·34 (SD 3·40; p=0·0009 vs baseline). DBS was associated with significant improvements in measures of depression (mean Hamilton Depression Rating Scale scores 19·40 [SD 6·76] at baseline vs 8·79 [7·64] at 12 months; p=0·00015), anxiety (mean Beck Anxiety Inventory score 38·00 [15·55] vs 27·14 [18·39]; p=0·035), and affective regulation (mean Dysfunction in Emotional Regulation Scale score 131·80 [22·04] vs 104·36 [31·27]; p=0·019). We detected significant changes in cerebral glucose metabolism in key anorexia nervosa-related structures at both 6 months and 12 months of ongoing brain stimulation. Interpretation: In patients with chronic treatment-refractory anorexia nervosa, DBS is well tolerated and is associated with significant and sustained improvements in affective symptoms, BMI, and changes in neural circuitry at 12 months after surgery. Funding: Klarman Family Foundation Grants Program in Eating Disorders Research and Canadian Institutes of Health Research.